CONTACT-INHIBITED REVERTANT CELL LINES ISOLATED FROM SV40-TRANSFORMED CELLS : II. Ultrastructural Study - McNutt, N. Scott (The Rockefeller University Press, 1971)
The ultrastructural appearances of normal 3T3, SV40-transformed 3T3 (SV-3T3), and F1A revertant cell lines are compared. Both confluent and subconfluent cultures are described after in situ embedding of the cells for electron microscopy. There is striking nuclear pleomorphism in F1A revertant cells, with many cells having large nuclei compared to the less variable nuclear morphology of both normal 3T3 and SV-3T3 cells. Under the culture conditions used, deep infoldings of the nuclear envelope are prominent in growing cells, e.g., subconfluent normal 3T3 and confluent SV-3T3 cells. Such infoldings are infrequently seen in cultures which display contact inhibition of growth, e.g., normal 3T3 or F1A revertant cells grown just to confluence. In confluent cultures, the cytoplasmic organelles in revertant cells closely resemble those of normal 3T3 cells. In both normal and revertant cells in confluent culture, the peripheral cytoplasm (ectoplasm) has many 70 A filaments (alpha filaments), which are frequently aggregated into bundles. Alpha filaments are also abundant in the ectoplasm near regions of cell-to-cell apposition and in the motile cell processes (filopodia). The abundance and state of aggregation of alpha filaments correlates with contact inhibition of movement and growth in these cell lines since fewer bundles of alpha filaments are seen in growing cells than in contact-inhibited cells. This observation suggests that these filaments may be an important secondary component in the regulation of contact inhibition of movement and, possibly, of growth in normal and revertant cells.